PENERAPAN PEMBELAJARAN VIRTUAL CLASS PADA MATERI TEKS EKSPLANASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS XI IPS 2 SMA 1 KUDUS TAHUN 2017 - Eko Nur Budi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
Formulation of research problem was (1) How to apply Virtual Class learning of Explanatory Text Material to class XI IPS 2 students in SMA 1 Kudus in 2017; 2) Is the Virtual Class learning of Explanatory Text material able to increase student activity of class XI IPS 2 in SMA 1 Sudus in 2017?; 3) Is the Virtual Class learning of Explanatory Text material able to improve the learning outcomes of Indonesian Language of class XI IPS 2 students in SMA 1 Kudus in 2017? The research used two cycles of Classroom Action Research design. Based on the data analysis, it resulted in preliminary data of minimum value of 60, maximum value of 80, average value of 70.2, and mastery learning of 83.3%. Research data of cycle I indicated the achievement of minimum value by 65, maximum value of 92.5, average value of 79.8, and mastery learning of 96.3%. Research data on cycle II represented the attainment value of at least 70, maximum value of 90, average value of 84.83, and mastery learning of 100%. Similarly, student activity in cycle II showed an increase by 95% in category B (good).